The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1161/01.hyp.23.2.244
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four-hour blood pressure and heart rate profiles in humans. A twin study.

Abstract: To delineate the relative roles of genetic and environmental factors on physiological variations of blood pressure and heart rate, we performed 24-hour ambulatory blood pressure monitorings with simultaneous polygraphic sleep recordings in 28 monozygotic and 16 dizygotic healthy young male twin pairs investigated in a standardized physical and social environment. Blood pressure and heart rate were measured every 10 minutes for 24 hours. A best-fit curve based on the periodogram method was used to quantify chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 26 publications
2
34
1
1
Order By: Relevance
“…19 Dipper/nondipper status is largely thought to be genetically predetermined, 13 as has been shown in a monozygotic twin study, 14 but such changes have also been reported to be influenced by individual physical activity, 25 sleep quality, 26 nocturnal urination, 27 and sleeping posture. 28 In this study, we used the same subjects to compare these measurements at different times.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…19 Dipper/nondipper status is largely thought to be genetically predetermined, 13 as has been shown in a monozygotic twin study, 14 but such changes have also been reported to be influenced by individual physical activity, 25 sleep quality, 26 nocturnal urination, 27 and sleeping posture. 28 In this study, we used the same subjects to compare these measurements at different times.…”
Section: Resultsmentioning
confidence: 97%
“…However, studies of 24-h BP changes have found genetic predisposition to play a major role in circadian rhythm. 13,14 Therefore, the results of the above studies may be confounded by genetic disposition and/or familial factors. What we do not know is how changes in BP measurement would be affected by shift work in the same group of subjects.…”
mentioning
confidence: 99%
“…For example, heart rate, blood pressure, and cardiac output all exhibit circadian rhythmicity in humans and animal models [2][3][4][5]. The onset of myocardial infarctions (MIs) also exhibit a marked circadian rhythm in humans, with increased incidence in the early hours of the morning [6].…”
Section: Introductionmentioning
confidence: 99%
“…Oscillations in cardiovascular functions are firmly established, including time-of-day-dependent fluctuations in blood pressure, heart rate, and cardiac output (9,10,31). Night shift work and frequent time zone changes result in a dissociation between this intrinsic timekeeping mechanism and the environment, which is associated with increased risk of adverse cardiovascular effects (such as myocardial infarction and sudden cardiac death) (5,15,33).…”
mentioning
confidence: 99%